Peer Support Group as a Community-Based Strategy for Depression Management - Dhaifatu Dzulilmi; Devi Shanti Prameswari; Reza Rizwandipa Wahyudi (Indonesian Publication Center, 2026)
Depression is a common mental disorder today. It is estimated that 280 million people are affected by depression globally. The American Psychological Association (APA) recommends initiation of depression therapy using psychotherapy and pharmacological methods. Both methods can be used together or administered separately. Psychotherapy in cases of depression has various methods, one of which is community-based therapy. Community-based therapy focuses on maintaining, protecting, preventing, and improving the health status of population groups and communities. This form of treatment plays an important role in prevention and can be part of current mental health services. Community-based therapy has various approaches such as peer-support, group- based activities, and even therapy through online media. Based on this, we are interested in designing a literature review that aims to analyze the effectiveness of community-based peer support therapy and involves a group of individuals with similar life experiences.